Financial System Development, Regulation and Economic Growth : Evidence from Russia - Ulrich Thießen (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
Recent contributions to the empirical analysis of the relationship between financial system development and economic growth found that an exogenous component of financial system development causes economic growth, is a good predictor of growth and that its growth impact is relatively large. In addition, the empirical literature on banking crises predicts that their adverse effects on economic growth will rise in the absence of an adequate response by the government. Given these findings and considering that the Russian government failed to respond adequately to the 1998 banking crisis, Russia?s strong economic growth since the crisis is a puzzle. The paper attempts to analyze Russia?s growth process and to empirically make visible the impact of the banking crisis. It is found that the growth costs of the crisis may have been even larger than suggested by a simulation that uses growth coefficients from the literature. This adverse growth impact was compensated by other expansionary effects. The finding corroborates those studies that argue for the importance of financial system development in promoting growth in transition countries.
Keywords: O40; O16; G28; C53; 330; Financial system stability; economic growth; banking crisis; Finanzsektor; Wirtschaftswachstum; Bankenkrise; Bankenpolitik; Schätzung; Russland